Fuel Grade Ethanol Production by Batch Distillation Using Ternary Components - I Gusti S Budiaman; Tjukup Marnoto; Chintya Rizki Hapsari; Risqi Angga Yudha Prakosa (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Ethanol is a chemical compound whose production is abundant in Indonesia. Ethanol is also widely used in the pharmaceutical industry, cosmetics, solvents, and spiritus fuel. Pure ethanol also has a high octane rating making it suitable used to raise the octane number of the gasoline. One way that can be done to purify the ethanol is a way to shift the ternary distillation azeotrope so that its purity can reach over 99.5%. Chemicals used to raise the boiling point of water include sulfuric acid, sodium hydroxide, ethylene glycol, glycerol and citric acid at certain concentrations. Ternary components were added to the raw material alcohol 86% specified in such order to obtain increasing boiling point of water as the heavy fraction by 5 oC, 10 oC, 15 oC, 20 oC and 25 oC.The distillation process is done in batch include column packing material at atmospheric pressure. Distilled provide 99.57% up to 99.91% purity ethanol in ternary addition of sulfuric acid, 99.59% up to 99.79% in the ternary addition of sodium hydroxide, 99.55% in the ternary addition of ethylene glycol, 99.64% on a ternary addition of glycerol, and 99.42% in ternary addition of citric acid. So in this experiment only the addition of sulfuric acid ternary who can give the best results with ethanol content 99.91%.